Analisis Penerapan Teknologi dalam Pembelajaran Pendidikan Agama Islam - Muhammad Sulaiman; Trisna Rukhmana; Irawan Irawan; Muhammadong Muhammadong; Gamar Al Haddar; Asep Supriyanto (Journal on Education, 2024)
This research aims to examine the impact of applying technology in learning Islamic Religious Education. Through a qualitative approach with a case study design, this research focuses on the integration of multimedia, online learning platforms, and interactive applications in the Islamic Religious Education curriculum. The research results show that the application of technology has a positive impact on student engagement, positive student responses to more dynamic learning methods, and challenges related to limited access to technology. Support and training for teachers was also found to be a key factor. The implications of the results of this research for curriculum development and efforts to provide equitable access to technology in the context of Islamic learning are also discussed